The Effect of Teacher's Aides in the Classroom: Evidence from a Randomized Trial - Andersen, Simon Calmar; Beuchert, Louise; Nielsen, Helena Skyt; Thomsen, Mette Kjærgaard (Social Science Research Network, 2016)
Countries around the world use teacher’s aides to support students, although there is no strong evidence of any positive impact on student outcomes. We use a randomized trial to challenge this state of evidence. We compare two treatment groups — aides with and without teaching degrees — to a control group. With a fixed budget, assistants without formal teaching qualifications can spend more time in the classrooms and tend to have a greater impact on students than co-teachers with a formal degree. These results are consistent with the notion that the teaching dosage is important for the positive effect of teacher’s aides